Sarfa as one of the miraculous aspects of The Quran between the supporters and opponents, review and study - Al-Maliki, Shahd Atwan Saleh (Journal of Islamic Sciences, 2023)
This study aims to understanding the opinions of both sides regarding “Sarfa” and determining the correct view on whether or not it is one of the miraculous aspects of the Quran. The study utilizes criticism, analysis, and comparison of the opinions of scholars. The main findings include: the definition of “Sarfa” according to Al-Nizham, Al-Jahizh, Al-Asbahani and Al-Rumani is a miracle made by Allah to prevent the Arabs from challenging the Quran. They were capable of doing so, but they were prevented by an external factor, causing a miracle, but if they had not been prevented by that factor, they would have brought something like the Quran. According to Al-Sharif Al-Murtada and Ibn Sinan Al-Khafaji, “Sarfa” means that Allah deprived the Arabs of the knowledge that would have enabled them to challenge the Quran; and this “Sarfa” is a miracle. A third view adopted by Al-Fakhr Al-Razi, Ibn Kathir and Al-Alusi states that the original rule in the Quran is that it is miraculous by itself. The advocates of “Sarfa” do not have any convincing evidence, from the Quran & Sunnah or logical evidence, to support their claims. Moreover, their view was based on illusions and weak evidence.
Keywords: Holy Quran; Quranic miracle; Quran challenge